HUMAN CAPITAL AS MODERATING THE EFFECT OF FOREIGN INVESTMENT AND FOREIGN DEBT ON ECONOMIC GROWTH - Azam Asykarulloh; Joko Setyono; Mayogi Araffi; Rosihaturrosyidah Rosihaturrosyidah; Ahmad Ulil Albab Al Umar (Jurnal Ekonomi, 2023)
For developing countries, development requires capital including foreign investment and foreign debt. The capital that has been collected will then be optimally managed by good human resources so that it can produce economic growth. This study attempts to examine the effect of foreign investment and foreign debt on economic growth with the Human Development Index as a moderating variable. The findings of this study indicate that foreign investment has a direct positive effect on economic growth. Foreign debt has a negative effect on economic growth. Meanwhile, the Human Development Index can only moderate foreign debt variables and provide a positive influence.